Implementasi Good Corporate Governance di OJK Sumatera Utara dalam Mendorong Stabilitas Sistem Keuangan Daerah - Cici El Dirrah Syafitri; Anggun Khairunnissa Agustin; Haura Afnani Zanjabila; Syahla Nabila; Ahmad Wahyudi Zein (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
This study evaluates the implementation of Good Corporate Governance (GCG) by the Financial Services Authority (OJK) Regional Office 5 North Sumatra in maintaining regional financial system stability. Applying the TARIF principles (Transparency, Accountability, Responsibility, Independence, Fairness), OJK executes an integrated Risk-Based Supervision (RBS) mechanism. The results indicate that transparency through multi-channel performance publication and institutional independence from local political intervention have proven effective in mitigating systemic risks. This governance success is confirmed by solid financial stability indicators, specifically North Sumatra's economic growth of 5.03% (2024) and a controlled banking Non-Performing Loan (NPL) ratio. The study concludes that strengthening GCG in supervisory functions is positively correlated with banking liquidity resilience and market confidence in North Sumatra.